Percepção de professores sobre o autismo em alunos pré-escolares e a rede social institucional. - Couto, Cirleine Costa (2017)
The early diagnosis of Autism Spectrum Disorder – ASD – is a fundamental condition to obtain better results in therapeutic interventions. The synergic articulation between education and health professionals is an effective strategy for hosting suspected cases and immediate referral to specialized care services in the area. Given this scenario, this research aimed to know the perception of the teachers of Early Childhood Education on the TEA and the institutional support network built from the suspect cases. It was assumed that the teachers' understanding of autism could still be insufficient, and that the institutional social network linked to the Municipal Infant Education Centers – CMEIs – to support children with suspected ASD in Foz do Iguaçu was not well constituted. The development of research has taken place through the qualitative approach. The field of research consisted of 10 CMEIs of the northern region of the city, place of greater concentration of school units. One teacher from each CMEI was selected, totaling 10 participants. The inclusion criteria were teachers with more than 3 years of teaching experience and acting at levels above that of the nursery. The data collection was done through semi-structured interviews and the construction of the minimum map of the institutional social network, carried out with the teachers, between September and December 2016. For the treatment and analysis of the data, the analysis was used content, thematic modality. Institutional social network maps were interpreted in the light of the criteria described by Walter Ude, of the principle of integrality in care and the Psychosocial Attention Networks recommended by the Ministry of Health for individuals with ASD in Brazil. From the analysis of participants' speeches, we observed that teachers have knowledge about the main characteristics of ASD, despite the need to clarify the wide phenotypic variety of the disorder. The impact of the teacher's experiences with the TEA in the classroom was a recurring theme in the speeches. In the analysis of the minimum network maps, it was observed that the main support of the schools in hosting the suspected cases of ASD was the direction or coordination of the SMEs, families and professionals of the "Building Citizenship Program". It was considered that, despite the need for further clarification, teachers are currently able to identify students with suspicious signs of ASD in the classroom, and can be included in the Psychosocial Attention Network as autism tracing agents. It was also pointed out that the institutional social network supporting the school in Foz do Iguaçu is still precarious, and therefore needs to be reformulated and strengthened.